TAZIBOUHO-UNIVERSITÉ'S FRAGMENTED MARKET (DALOA, CÔTE D’ IVOIRE): - Mohamed KANATE (Finisterra - Revista Portuguesa de Geografia, 2024)
Markets are important to public decision-makers in Côte d'Ivoire, who are constructing communal markets. The commune of Daloa serves as an example: apart from its central market, each district hosts a secondary market. However, despite this infrastructure, the Tazibouho-Université district features individual markets dispersed throughout densely populated areas. This scattered distribution, with limited spheres of influence, contradicts the evolutionary principle of markets. Market fragmentation diminishes the exchange of goods and services, despite its prevalence in Tazibouho-Université. This article analyzes the underlying reasons for this situation, which opposes the natural dynamics of markets. To achieve this, a literature review on markets was conducted, followed by a field survey involving merchants, customers, and suppliers. Additionally, a geographic information system was utilized to establish causal relationships and connections among stakeholders and services. This allowed us to demonstrate that this market arose from the intersection of the district's social structure and spatial organization, leading merchants to cater to local residents as customers and receive supplies from other markets and distant farmers. Furthermore, its expansion is attributed to the socio-professional status of local civil servants, whose purchasing behavior is influenced by the proximity strategies employed by merchants.